Особливості ментальності українського народу в пошуку національної ідеї та впливу їх на соціалізацію особистості - П'ятенко, В. Г. (НТУ "ХПІ", 2009)
Атором розкрито сутність економічної кризи у суспільстві. Проаналізовано умови її виникнення та вказано на можливі шляхи її подолання, основа яких в особливостях ментальності українського народу.

Author essence of economic crisis in the company is exposed. The terms of its origin are analysed and it is indicated on the possible paths of its overcoming, basis of which in the features of mentality of the Ukrainian people.
Features of mentality of Ukrainian people in search of national idea and influencing of them on socialization of personality
Keywords: криза економічна; суспільство; ідеологія